Digital or Print? A Comparison of Preschoolers' Comprehension, Vocabulary, and Engagement From a Print Book and an e-Book - Stephanie M. Reich; Joanna C. Yau; Ying Xu; Tallin Muskat; Jessica Uvalle; Daniela Cannata (SAGE Publishing, 2019)
Increasingly, children are engaging in early literacy experiences through digital devices. This raises questions about how electronic reading compares to print reading. To assess this, we randomly assigned 200 children (3-5 years) to be read the same book (1) with auto-narration on a tablet or 2) by a researcher from a print book. Reading was recorded and coded for behavioral and emotional engagement and vocalizations. Children were also tested on their story comprehension and vocabulary. Children had slightly higher posttest scores in the print condition. Older children and females also scored higher. There was an interaction between weekly tablet use and book platform. Children were equally engaged with the e-book and print book, but vocalized more about the device in the e-book condition. Findings suggest that e-books offer many of the same, but not all, of the educational affordance as print books. Additionally, novelty might be important in supporting comprehension.